Collaborative Governance Program Patriot Desa Dalam Mengembangkan Potensi Desa di Jawa Barat - Vita Khairunnisa Mula; Milwan Milwan; Heri Wahyudi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study analyzes collaborative governance in the Patriot Desa Program by examining how multi-actor collaboration works at the village level, particularly in villages with stagnant Village Development Index (IDM) scores such as Situhiang. The research addresses the paradox between IDM improvement and weak institutionalized collaboration in assisted villages. The study aims to describe the dynamics of collaborative governance in planning and implementing the program at village level and to identify factors that limit the effectiveness and sustainability of collaboration. A qualitative descriptive approach with a case study design was employed through in-depth interviews, document analysis, and observation of provincial government actors, Patriot Desa officers, village governments, and local community leaders, using the Collaborative Governance Regime framework as an analytical lens. Findings show that collaboration opens participatory spaces and builds shared motivation at the grassroots, yet agenda setting and strategic decisions remain dominated by bureaucratic actors. Joint action capacity grows through the strengthening of local champions and initiatives based on village potentials, but resource asymmetries, actor rotation, and program cycles make collaboration largely project-based and hinder its transformation into an institutionalized governance regime. The study concludes that collaborative governance in the village context tends to take the form of an administrative collaboration regime, in which institutional trust, adaptive learning, and cross-actor policy integration are still limited. The research offers novelty by presenting a village-level perspective on how collaborative governance operates and encounters structural limits, while pointing to the need for stronger institutional design, more balanced role distribution, and post-program sustainability strategies.